SIMBOL-SIMBOL NASIONALISME DALAM FILM GURU BANGSA: TJOKROAMINOTO - Mutiara Endah Suciati; Mochamad Ilham; Soekma Yeni Astuti (Program Studi Film dan Televisi Universitas Jember, 2018)
ABSTRACTGuru bangsa: Tjokroaminoto is a biographical genre film with the theme of nationalism.It is a film that tell one Indonesia’s historical figures, HOS Tjokroaminoto who has a spirit ofnationalism as he is willing to leave his noble status. Released in 2015, directed by GarinNugroho. The nasionalism symbol purposed to makes envinroment more know about a nationalidentivy. It can be enjoyable in every media, includes film. Based on the description above, theresearcher is interesting to comprehend the symbols of nationalim in the film of Guru Bangsa:Tjokroaminoto. The type of this study is descriptive qualitative which will be used to obtain theresult that have an important role in conveying the symbols of nationalism in the movie GuruBangsa: Tjokroaminto based on Christian Metz’s theory of semiotics presented through the mise-en-scene aspect.